Innovation Practices for Survival of Trading Small and Medium Enterprises - Khongrat, Etty (Universitas Prasetiya Mulya, 2025)
This study aims to develop a theoretical model to provide insights about the association between innovation practices and the SMEs’ performance and survival while underlining the auxiliary role of external support in such a relationship. Global epidemic crises, such as the coronavirus usually expose small and medium enterprises (SMEs) to various kinds of challenges and may put their at risk. Online questionnaire has been used to collect the data from 125 randomly selected SMEs managers Jakarta Polytechnic Alumni. The data was analyzed using the SmartPLS3 software. The structural equation modeling results showed that the innovation practices adopted by SMEs to face the repercussions of environmental changes had a positive impact on the performance and likelihood of business survival. PLS-SEM bootstrap results indicated that external support aids strengthen the positive impact of SMEs innovation practices on business survival rather than its performance. The theoretical implication of this study is that business performance and survival are a strong package to face various situations and conditions. The study has several significant practical implications for SMEs managers, governments, and policy makers that have been stated.